Tablet Pemurni Air Yang Terkontaminasi Logam Berat Dengan Memanfaatkan Limbah Kerang Darah (Tegillarca Granosa) - I Wayan, Marlon Managi; Arsani, Ida Ayu Anom; Wimargamal, Natan (Jurnal Mekanik Terapan, 2025)
Water pollution caused by heavy metals such as lead (Pb) poses a serious threat to both environmental and human health. One promising solution involves the use of natural materials derived from organic waste as adsorbents, such as blood clam shells (Tegillarca granosa), which are rich in calcium carbonate (CaCO₃) and exhibit high potential following calcination. This study aims to evaluate the effect of calcination temperature variation on the adsorption efficiency of clam shells in tablet form for Pb²⁺ ions. The calcination process was conducted at temperatures of 400°C, 650°C, and 900°C for 2 hours each, following an initial drying stage at 150°C for 1 hour. The resulting calcined powder was ground, sieved, and compressed into tablets using a mechanical pressure of 150 N. Adsorption tests were carried out using a Pb solution with a concentration of 38.9 ppm for 1 hour, and the residual concentration was analyzed using Atomic Absorption Spectrophotometry (AAS). The results showed that calcination at 400°C yielded the highest adsorption efficiency at 99.3%, followed by 650°C (99.1%) and 900°C (98.4%). These findings indicate that calcination temperature significantly influences the characteristics and performance of the adsorbent, highlighting the potential of calcined blood clam shell waste as an effective and sustainable alternative for removing heavy metal contaminants from polluted water.